Pharmacologically potentials of hydrazonone containing compounds: a promising scaffold - Asif, Mohammad (International Journal of Advanced Chemistry, 2014)
Hydrazones considered as an important class of compounds for new drug development. Hydrazones are present in many of the bioactive compounds having wide interest because of their diverse biochemical applications. This created interest in researchers to developed variety of hydrazone compounds with effective biological activities. Therefore many compounds have been developed as target structures for their biological activities. This review is focus on the diverse biological activities of hydrazones. Keywords: Hydrazones, Biological Activities, Azomethine, Pharmacological Potential.